Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Using novel methods to model non-carbon dioxide (non-CO2) emissions and associated climate response of real-world flights - Conor Gallagher; Stephen Spence; Charles Stuart (Journal of Cleaner Production, 2026)

Effect of six weeks ubiquinol supplementation on mitochondrial respiratory function and exercise capacity in healthy males - Jarred P. Acton; Nehal S. Alsharif; Jack W. Bond; Stuart P. Cocksedge; Abbie G. Mclellan; Donald L. Peden; Mark P. Funnell; Hannah F. Dugdale; Lewis J. James; Richard A. Ferguson; Tom Clifford; Stephen J. Bailey (European Journal of Applied Physiology, 2026)
Coenzyme Q10 (CoQ 10 ) is an integral component of the mitochondrial electron transfer system. Most studies have administered the oxidised form of CoQ 10 (ubiquinone) and observed no effects on mitochondrial respiratory function or endurance exercise performance. The reduced form of CoQ 10 , ubiquinol (UQH 2 ), has greater bioavailability than ubiquinone, but the effects of UQH 2 supplementation on mitochondrial respiratory function and exercise capacity are unclear. Fifty-four healthy, recreationally active males were randomised to receive either 300 mg·day − 1 UQH 2 or placebo (PLA) for 6 weeks in a double-blind independent-group design. Before and after the supplementation period, skeletal muscle mitochondrial respiration variables and protein content of the mitochondrial leak proteins, adenine nucleotide translocase1 + 2 (ANT1 + 2) and uncoupling protein-3 (UCP-3), were assessed. In addition, participants completed a severe-intensity cycle test to exhaustion to assess time to the limit of tolerance (T Lim ) and oxygen uptake (V̇O 2 ) kinetics. Compared to pre-supplementation and PLA, UQH 2 supplementation increased plasma [CoQ 10 ] ( P < 0.05), and lowered inverse respiratory control ratio (Pre-PLA: 0.064 ± 0.034 vs. Post-PLA: 0.072 ± 0.026; Pre- UQH 2 : 0.073 ± 0.039 vs. Post-UQH 2 : 0.044 ± 0.019; P < 0.05), suggestive of improved oxidative phosphorylation coupling efficiency. There were no differences in ANT1 + 2 or UCP-3 protein content post-supplementation compared to pre-supplementation between groups ( P > 0.05). End-exercise V̇O 2 , change in V̇O 2 between 2 min and end-exercise, and T Lim were not different between groups post-supplementation ( P > 0.05). Six-weeks UQH 2 supplementation increased plasma [CoQ 10 ] and oxidative phosphorylation coupling efficiency, but did not alter mitochondrial leak proteins, T Lim or V̇O 2 kinetics during severe-intensity exercise in healthy, active males.

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Air pollution and cardio-respiratory mortality in Limpopo, South Africa (2011–2020): evidence on population and seasonal vulnerability - Stephen Balaka Opiyo; Roelof Burger; Martha Nafula Balaka; Stuart Piketh (Air Quality, Atmosphere & Health, 2026)
Ambient air pollution is a growing public health concern in South Africa. However, the health impacts of ambient air pollution in the country remain largely unquantified, a gap that is consistently reflected in global systematic reviews. This study investigates the association between ambient air pollution and cause-specific mortality, cardiovascular (CVD), and respiratory disease (RD), in Limpopo province, South Africa, over a decade from 2011 to 2020, with the aim of unravelling population and seasonal vulnerability. Daily mortality data were sourced from Statistics South Africa, while ambient air pollutant concentrations (PM₁₀, PM₂.₅, SO₂, NO₂, and O₃) were retrieved from the South African Air Quality Information System. Time-series and quasi-Poisson regression models within a generalized additive model framework were employed to estimate relative risks (RRs) per interquartile range (IQR) increase in pollutant concentrations, adjusting for seasonality and meteorological covariates. A total of 73,167 CVD and 62,248 RD deaths were recorded during the study period. PM and O₃ emerged as the strongest predictors of excess mortality, with O₃ particularly linked to CVD mortality and PM to RD mortality. An interquartile range increase in O₃ was associated with a 0.3–7.5% increase in CVD and RD mortality across subgroups, while PM₂.₅ showed smaller but significant increases, ranging from 0.3 to 1.2% across subgroups for CVD and RD mortality. Notably, SO₂ and NO₂ exhibited weaker and more variable effects, often manifesting at delayed lags. Vulnerable populations, particularly women, older adults (65+), and certain outdoor-exposed workers, experienced greater mortality risks, highlighting the differential susceptibility of specific subgroups. Seasonal analysis revealed elevated mortality and pollutant concentrations during the cold compared to the warm period. Short-term exposure to ambient air pollution is associated with increased cardio-respiratory mortality in Limpopo Province, with stronger effects for ozone and particulate matter and heightened vulnerability during the cold season, highlighting the need for targeted public health and regulatory interventions.

Changes in Key Biodiversity Area networks following national comprehensive assessments - Andrew J. Plumptre; Zoltan Waliczky; Daniele Baisero; Olivia Crowe; Jeannot Kivono; Cecilia Tobar; Maria Gabriela Toscano; Natalia Boulad; Hugo Costa; Camila Davila; Sophie Dirou; Eleuterio Duarte; et al. (Conservation Biology, 2026)
Key Biodiversity Areas (KBAs) are sites of significance for the global persistence of biodiversity. Based on the Global Standard for the Identification of Key Biodiversity Areas (KBA Standard), published in 2016, sites are currently being assessed for KBA designation in a growing number of countries across the world. For these assessments, the KBA criteria are applied to all species and ecosystems with available data. We reviewed the first comprehensive assessments of 11 countries and compared the KBA network before and after assessments. The mean (SD) number of KBAs per country increased by 69.6% (102.1), and the mean total extent of KBAs per country increased by 164.2% (150.7). More than half of the KBAs in 2024 had >50% of their area outside the 2019 KBAs, indicating a substantial increase in KBA extent (54.0% [18.8] of KBAs). The mean proportion of each KBA covered by protected or conserved areas decreased from 56.2% (20.2) to 44.5% (15.5), owing to the incorporation of unprotected sites in the KBA network. On average, 41.1% (14.0) of sites in each country (mean 44.5 [46.4] sites per country) and 47.2% (20.5) of new KBA area after the assessment were completely unprotected, indicating that many of the new sites were not recognized in national protected area networks as significant for biodiversity before the assessment. Making a comprehensive assessment of KBAs increased the combined coverage of protected and conserved area networks from 25.4% (10.6) to 32.0% (13.1) in each country and thus contributed to reducing biodiversity loss. Therefore, comprehensive assessments of KBAs led to a substantially increased number and extent of recognized sites of importance for biodiversity published in the World Database of KBAs. Where such assessments have not been made, many important areas for biodiversity may be overlooked. We therefore encourage other nations to update their KBA networks to inform efforts to meet the goals and targets of the Kunming–Montreal Global Biodiversity Framework.

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Hindsight informs foresight: revisiting millennial forecasts of impacts and status of rocky shores in 2025 - Stephen J. Hawkins; Kathryn A. O'Shaughnessy; George M. Branch; Laura Airoldi; Simon Bray; Paul Brooks; Michael T. Burrows; Juan Carlos Castilla; Tasman P. Crowe; Thomas W. Davies; Louise B. Firth; Keith Hiscock; et al. (Marine Pollution Bulletin, 2025)

ESG mapping of the Australian mining sector – The state of play on mobilising spatial datasets for decision making - Eléonore Lèbre; Karol Czarnota; Stuart D.C. Walsh; Marcus Haynes; Natasha Ufer; Laura J. Sonter; Rachakonda Sreekar; Pascal Bolz; Nevenka Bulovic; Claire Côte; Nadja C. Kunz; Steven Micklethwaite; et al. (Resources Policy, 2025)

Modelling and mapping of subsurface nitrate-attenuation index in agricultural landscapes - Stephen B. Collins; Ranvir Singh; Stuart R. Mead; David J. Horne (Journal of Environmental Management, 2025)

A highly prevalent and specific cryptic plasmid pBI143 for human fecal pollution tracking in a subtropical urban river - Yawen Liu; Wendy J.M. Smith; Metasebia Gebrewold; Rory Verhagen; Stephen Cook; Stuart L. Simpson; Bethany Oceguera Johnson; Kyle Bibby; Warish Ahmed (Water Research, 2025)

Development and in-vitro assessment of novel oxygen-releasing feed additives to reduce enteric ruminant methane emissions - Alison Graham; Camilla Thorn; Michael McDonagh; Caroline O'Donnell; Stephen Nolan; Stuart F. Kirwan; Sandra O'Connor; Corine O. Nzeteu; Alejandra C.V. Montoya; Andrew Bartle; Alison Hall; Cathy Abberton; et al. (Science of The Total Environment, 2025)

Assessment of spatial variability and temporal stability of groundwater redox conditions in New Zealand - Stephen B. Collins; Ranvir Singh; Stuart R. Mead; David J. Horne; Jon K. F. Roygard (Environmental Monitoring and Assessment, 2024)

Comparison of three reanalysis‐driven regional climate models over New Zealand: Climatology and extreme events - Isaac Campbell; Peter B. Gibson; Stephen Stuart; Ashley M. Broadbent; Abha Sood; Amir A. S. Pirooz; Neelesh Rampal (International Journal of Climatology, 2024)
Three ~12‐km reanalysis‐driven regional climate models (RCMs) are evaluated in terms of capturing climatologies and extremes of precipitation, temperature and surface wind over Aotearoa/New Zealand (NZ). NZ provides an excellent case study for evaluating high‐resolution RCMs due to its coastal and complex terrain and isolated geographical position in the midlatitudes, exposed to both tropical and polar influences. Overall, we find that the RCMs faithfully reproduce the observed climate, with precipitation and temperature climatologies particularly well‐captured. However, the RCMs display significant differences from observations in capturing the surface wind climatology, highlighting a remaining key challenge. The excess “drizzle problem” is apparent to varying degrees, leading to a weaker representation in the length of meteorological drought in some regions. The RCMs also diverge in reproducing diurnal temperature range which appears partly related to cloud cover. Finally, we discuss the important role of observational uncertainty in the context of model evaluation.

Lead-up and manifestation of the Oceanic Anoxic Event 2 at the DSDP Site 398 (Vigo Seamount, NW Iberian offshore): Palynological and geochemical insights - Iván Rodríguez-Barreiro; Artai A. Santos; Uxue Villanueva-Amadoz; Stephen Louwye; Stuart A. Robinson; José B. Diez (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Dynamical downscaling CMIP6 models over New Zealand: added value of climatology and extremes - Peter B. Gibson; Stephen Stuart; Abha Sood; Dáithí Stone; Neelesh Rampal; Hamish Lewis; Ashley Broadbent; Marcus Thatcher; Olaf Morgenstern (Climate Dynamics, 2024)
Dynamical downscaling provides physics-based high-resolution climate change projections across regional and local scales. This is particularly important for island nations characterized by complex terrain, where the coarse resolution of global climate model (GCM) output often prohibits direct use. One of the main motivations for dynamical downscaling is to reduce biases relative to the host GCM at the local scale, which can be quantified through assessing ‘added value’. However, added value from downscaling is not guaranteed; quantifying this can help users make informed decisions about how best to use available climate projection data. Here we describe the experiment design of the updated national climate projections for New Zealand based on dynamical downscaling. The global non-hydrostatic Conformal Cubic Atmospheric Model (CCAM) is primarily used for downscaling, with a global stretched grid targeting high resolution over New Zealand (12-km) and the wider South Pacific region (12–35-km). Focusing on the historical simulations, we assess added value for a range of metrics, climatological fields, extreme indices, and tropical cyclones. The main strengths of the downscaling include generally large improvements relative to the host GCM for temperature and orographic precipitation. Inter-annual variability in temperature is well captured across New Zealand, and several temperature and precipitation-based extreme indices show large improvements. The representation of tropical cyclones reaching at least category 2 intensity is generally improved relative to the large consistent under-representation in the host GCMs. The remaining biases are explored and discussed forming the basis for ongoing bias-correction work.

Moving to a new normal: Analysis of shifting climate normals in New Zealand - Raghav Srinivasan; Trevor Carey‐Smith; Linda Wang; Andrew Harper; Sam Dean; Gregor Macara; Ruotong Wang; Stephen Stuart (International Journal of Climatology, 2024)
New Zealand's National Institute of Water and Atmospheric Research publishes climate normals for New Zealand that are used for reporting the regional state of the climate, climate extremes and variability. Temperature and precipitation patterns are affected by both anthropogenic climate change and natural climate variability which in turn affect the climatological normal values calculated every decade. This study investigates how New Zealand's normals for temperature and precipitation have shifted over time at the national, regional and seasonal scales from the 1941–1970 period to the 1991–2020 period. Contrary to WMO recommendations, but aligned with many other countries, New Zealand's climate normals have traditionally not undergone homogenisation. The impact of introducing some homogenisation in the latest 1991–2020 normals, in contrast to historical non‐homogenized station normals, has been assessed using a new homogenized “Seventeen‐Station” temperature series from 1941 to 2020. We demonstrate that interpolating sparse non‐homogenized normals spatially to a grid can produce significant erroneous patterns and therefore undermine the accuracy of the conclusions drawn when using such normals. We find that the historical non‐homogenized temperature normals have a consistent negative bias in the long‐term trend at national, regional and seasonal scales. Our analysis of homogeneity tested precipitation showed consistent decreases at a national scale across all normal periods relative to the 1951–1980 precipitation normal. We also highlight how fixed period temperature and precipitation normals do not fully reflect the current state of a climate that is influenced by decadal variability and global warming. To derive normals fit for use in a changing climate it is suggested that automated methods for broad data homogenisation be developed along with alternative methods to derive normals that account for a non‐stationary climate.

Bottom simulating reflections across the northern Gulf of Mexico slope - Aditya Kumar; Ann E. Cook; Alexey Portnov; Stuart Skopec; Matthew Frye; Stephen Palmes (Marine and Petroleum Geology, 2024)

Rates of tree cover loss in key biodiversity areas on Indigenous Peoples’ lands - Ashley Thomas Simkins; Paul F. Donald; Alison E. Beresford; Stuart H. M. Butchart; Julia E. Fa; Alvaro Onrubia Fernández‐Llamazares; Stephen T. Garnett; Graeme M. Buchanan (Conservation Biology, 2024)
Indigenous Peoples’ lands (IPL) cover at least 38 million km 2 (28.1%) of Earth's terrestrial surface. These lands can be important for biodiversity conservation. Around 20.7% of IPL intersect areas protected by government (PAs). Many sites of importance for biodiversity within IPL could make a substantial but hitherto unquantified contribution to global site‐based conservation targets. Key Biodiversity Areas (KBAs) represent the largest global network of systematically identified sites of high importance for biodiversity. We assessed the effectiveness of IPL in slowing biodiversity loss inside and outside PAs by quantifying tree cover loss from 2000 to 2019 in KBAs at international and national levels and comparing it with losses at equivalent sites outside mapped IPL. Based on a matched sample of 1‐km 2 cells in KBAs inside and outside mapped IPL, tree cover loss in KBAs outside PAs was lower inside IPL than outside IPL. By contrast, tree cover loss in KBAs inside PAs was lower outside IPL than inside IPL (although the difference was far smaller). National rates of tree cover loss in KBAs varied greatly in relation to their IPL and PA status. In one half of the 44 countries we examined individually, there was no significant difference in the rate of tree cover loss in KBAs inside and outside mapped IPL. The reasons for this intercountry variation could illuminate the importance of IPL in meeting the Convention on Biological Diversity's ambition of conserving 30% of land by 2030. Critical to this will be coordinated action by governments to strengthen and enforce Indigenous Peoples’ rights, secure their collective systems of tenure and governance, and recognize their aspirations for their lands and futures.

Social-ecological vulnerability to environmental extremes and adaptation pathways in small-scale fisheries of the southern California Current - Fiorenza Micheli; Andrea Saenz-Arroyo; Emilius Aalto; Rodrigo Beas-Luna; Charles A. Boch; Juan Camilo Cardenas; Giulio A. De Leo; Eduardo Diaz; Antonio Espinoza-Montes; Elena Finkbeiner; Jan Freiwald; Stuart Fulton; et al. (Frontiers in Marine Science, 2024)
Coastal ecosystems and human communities are threatened worldwide by climate change, and shocks from social, market and political change. There is an urgent global need to promote resilient food production and livelihoods in the face of these shocks. Small-scale fisheries (SSF) in rural settings can be particularly vulnerable as they frequently lack the resources, rights and infrastructure to respond to shocks originating outside the focal systems. We examined ecological and social outcomes of environmental extremes in a SSF socio-ecological system (SES) by using long-term oceanographic (between 2010-2019) and ecological (2006-2018) data tracking change in a kelp forest ecosystem of Baja California, Mexico, and concurrent documentation of proactive and reactive actions of a fishing community organized in a cooperative. Results indicate a complex landscape of ‘winners’ and ‘losers’ among species and fisheries exposed to unprecedented environmental extremes, including marine heat waves and prolonged hypoxia, and a suite of adaptive actions by the local fishing cooperative, and others in the region, that have helped confront these rapid and drastic changes. Cooperatives have established voluntary marine reserves to promote recovery of affected populations and have invested in diversification of activities enabled by access rights, collective decision-making, and participatory science programs. Results indicate that local actions can support social and ecological resilience in the face of shocks, and that enabling locally-driven adaptation pathways is critical to resilience. This case study highlights the crucial importance of strengthening and supporting rights, governance, capacity, flexibility, learning, and agency for coastal communities to respond to change and sustain their livelihoods and ecosystems in the long run.

In vitro and in vivo accumulation of the anticancer Ru complexes [RuII(cym)(HQ)Cl] and [RuII(cym)(PCA)Cl]Cl - Mie Riisom; Stuart J. Morrow; Caitlin D. Herbert; William D. J. Tremlett; Jonathan W. Astin; Stephen M. F. Jamieson; Christian G. Hartinger (JBIC Journal of Biological Inorganic Chemistry, 2023)

Systemic innate myeloid responses to acute ischaemic and haemorrhagic stroke - Ruth Stephens; John R. Grainger; Craig J. Smith; Stuart M. Allan (Seminars in Immunopathology, 2023)
Acute ischaemic and haemorrhagic stroke account for significant disability and morbidity burdens worldwide. The myeloid arm of the peripheral innate immune system is critical in the immunological response to acute ischaemic and haemorrhagic stroke. Neutrophils, monocytes, and dendritic cells (DC) contribute to the evolution of pathogenic local and systemic inflammation, whilst maintaining a critical role in ongoing immunity protecting against secondary infections. This review aims to summarise the key alterations to myeloid immunity in acute ischaemic stroke, intracerebral haemorrhage (ICH), and subarachnoid haemorrhage (SAH). By integrating clinical and preclinical research, we discover how myeloid immunity is affected across multiple organ systems including the brain, blood, bone marrow, spleen, and lung, and evaluate how these perturbations associate with real-world outcomes including infection. These findings are placed in the context of the rapidly developing field of human immunology, which offers a wealth of opportunity for further research.

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

Inter-colony and inter-annual variation in discard use by albatross chicks revealed using isotopes and regurgitates - Amanda Kuepfer; Paulo Catry; Stuart Bearhop; Richard B. Sherley; Olivia Bell; Jason Newton; Paul Brickle; Alexander Arkhipkin; Stephen C. Votier (Marine Biology, 2023)
Effective marine ecosystem monitoring is critical for sustainable management. Monitoring seabird diets can convey important information on ecosystem health and seabird–fishery interactions. The diet of breeding black-browed albatross ( Thalassarche melanophris ) has previously been assessed using stomach content analysis (SCA) or stable isotope analysis (SIA), but not both methods together. Combining dietary sampling approaches reduces biases associated with using single methods. This study combines SCA and SIA to study the diet of black-browed albatross chicks, with a specific focus on fishery discard consumption, at two Falkland Islands colonies (New Island 51°43′S, 61°18′W and Steeple Jason Island 51°01′S, 61°13′W) during two consecutive breeding seasons (2019 and 2020). SCA provided high taxonomic resolution of short-term diet and priors for stable isotope mixing models, with multiple measures of dietary items (e.g. numeric frequency N%, frequency of occurrence FO%). By contrast, SIA of down feathers provided a single and more integrated dietary signal from throughout chick development. Although the two methods disagreed on the dominant prey group (SCA—crustacean; SIA—pelagic fish), the complementary information suggested a chick diet dominated by natural prey (SCA: 74%–93% [FO], 44%–98% [N]; SIA: minimum 87%–95% contribution). Nonetheless, SCA revealed that a high proportion of breeding adults do take discards. We detected consistent colony-specific diets in relation to prey species, but not in relation to higher discard use. Overall, discard consumption was highest in 2020, the year characterised by the poorest foraging conditions. Our results have implications for fisheries management and future dietary studies assessing discard use.

Occurrence of multiple respiratory viruses in wastewater in Queensland, Australia: Potential for community disease surveillance - Warish Ahmed; Aaron Bivins; Mikayla Stephens; Suzanne Metcalfe; Wendy J.M. Smith; Kwanrawee Sirikanchana; Masaaki Kitajima; Stuart L. Simpson (Science of The Total Environment, 2023)

An integrated approach to assessing abiotic and biotic threats to post‐fire plant species recovery: Lessons from the 2019–2020 Australian fire season - Rachael V. Gallagher; Stuart P. Allen; Berin D. E. Mackenzie; David A. Keith; Rachael H. Nolan; Libby Rumpff; Carl R. Gosper; Geoffrey Pegg; Stephen van Leeuwen; Mark K. J. Ooi; Colin J. Yates; Cory Merow; et al. (Global Ecology and Biogeography, 2022)
Aim Existing abiotic and biotic threats to plant species (e.g., disease, drought, invasive species) affect their capacity to recover post‐fire. We use a new, globally applicable framework to assess the vulnerability of 26,062 Australian plant species to a suite of active threats after the 2019–2020 fires. Location Australia. Time period 2019–2020. Major species studied Plants. Methods Spatial data for existing threats and information on species‐level susceptibility were combined with estimates of the extent of range burnt in southern Australia (> 22°S) to assign species against 10 criteria into vulnerability categories ( high , medium , low , none , data deficient ). We explore in detail results for three threats (drought, disease, feral animals), highlighting where impacts from multiple threats ranked high vulnerability may compound to reduce post‐fire recovery. Results Analysis of the full suite of 10 vulnerability criteria, which encompass a broad range of threats, revealed large numbers of species vulnerable to poor post‐fire recovery from one or more different hazards ( high vulnerability: 1,243 species; medium vulnerability: 2,450 species). Collectively, 457 plant species that burnt extensively (> 50%) across their range are highly vulnerable to poor recovery due to exposure to pre‐fire drought conditions (235 species), disease (186 species), or feral animals (97 species). Of these 457 species, 61 are vulnerable to more than one of these three threats, highlighting how a suite of interacting hazards can impact plant recovery after fire. Main conclusions While fire can renew plant populations by stimulating recruitment and resetting competitive interactions, the presence of existing threats in post‐fire landscapes jeopardizes recovery. The simultaneous impact of multiple threats that impact recovery can create a suite of hazards that contribute to declines and, potentially, extinction. Our method for rapid post‐fire vulnerability assessment can be applied to large numbers of plant species or other biota in fire affected regions globally.

Fire‐related threats and transformational change in Australian ecosystems - David A. Keith; Stuart P. Allen; Rachael V. Gallagher; Berin D. E. Mackenzie; Tony D. Auld; Sarah Barrett; Anne Buchan; Valerie English; Carl Gosper; Dave Kelly; Allen McIllwee; Rachel T. Melrose; et al. (Global Ecology and Biogeography, 2022)
Aim Megafire events generate immediate concern for wildlife and human well‐being, but their broader ecological impacts likely extend beyond individual species and single fire events. In the first mechanistic study of fire effects focussed on ecosystems, we aimed to assess the sensitivity and exposure of ecosystems to multiple fire‐related threats, placing impacts in the context of changing fire regimes and their interactions with other threats. Location Southern and eastern Australia. Time period 2019–2020. Major species studied Australian ecosystems. Methods We defined 15 fire‐related threats to ecosystems based on mechanisms associated with: (a) direct effects of fire regime components; (b) interactions between fire and physical environmental processes; (c) effects of fire on biological interactions; and (d) interactions between fire and human activity. We estimated the sensitivity and exposure of a sample of 92 ecosystem types to each threat type based on published relationships and spatial analysis of the 2019–2020 fires. Results Twenty‐nine ecosystem types assessed had more than half of their distribution exposed to one or more threat types, and only three of those were listed as nationally threatened. Three fire‐related threat types posed the most severe threats to large numbers of ecosystem types: high frequency fire; pre‐fire drought; and post‐fire invasive predator activity. The ecosystem types most affected ranged from rain forests to peatlands, and included some, such as sclerophyllous eucalypt forests and heathlands, that are traditionally regarded as fire‐prone and fire‐adapted. Main conclusions Most impacts of the 2019–2020 fires on ecosystems became apparent only when they were placed in the context of the whole fire regime and its interactions with other threatening processes, and were not direct consequences of the megafire event itself. Our mechanistic approach enables ecosystem‐specific management responses for the most threatened ecosystem types to be targeted at underlying causes of degradation and decline.

Associations of self-reported occupational exposures and settings to ALS: a case–control study - Stephen A. Goutman; Jonathan Boss; Christopher Godwin; Bhramar Mukherjee; Eva L. Feldman; Stuart A. Batterman (International Archives of Occupational and Environmental Health, 2022)
Background Environmental exposures contribute to the pathogenesis of amyotrophic lateral sclerosis (ALS), a fatal and progressive neurological disease. Identification of these exposures is important for targeted screening and risk factor modification. Objective To identify occupational exposures that are associated with a higher risk of ALS using both survey and standard occupational classification (SOC) coding procedures, and to highlight how exposure surveys can complement SOC coding. Methods ALS participants and neurologically healthy controls recruited in Michigan completed a detailed exposure assessment on their four most recent and longest held occupations. Exposure scores were generated from the exposure survey, and occupations were assigned to SOC codes by experienced exposure scientists. Results This study included 381 ALS and 272 control participants. ALS participants reported higher duration-adjusted occupational exposure to particulate matter (OR = 1.45, 95% CI 1.19–1.78, p < 0.001), volatile organic compounds (OR = 1.22, 95% CI 1.02–1.45, p = 0.029), metals (OR = 1.48, 95% CI 1.21–1.82, p < 0.001), and combustion and diesel exhaust pollutants (OR = 1.20, 95% CI 1.01–1.43, p = 0.041) prior to ALS diagnosis, when adjusted for sex, age, and military service compared to controls. In multivariable models, only occupational exposure to metals remained significant risk (OR = 1.56, 95% CI 1.11–2.20, p = 0.011), although in an adaptive elastic net model, particulate matter (OR = 1.203), pesticides (OR = 1.015), and metals (1.334) were all selected as risk factors. Work in SOC code “Production Occupations” was associated with a higher ALS risk. SOC codes “Building and Grounds Cleaning and Maintenance Occupations”, “Construction and Extraction Occupations”, “Installation, Maintenance, and Repair Occupations”, and “Production Occupations” were all associated with a higher exposure to metals as determined using survey data. Discussion Occupational exposure to particulate matter, volatile organic compounds, metals, pesticides, and combustion and diesel exhaust and employment in “Production Occupations” was associated with an increased ALS risk in this cohort.

Earth stewardship: Shaping a sustainable future through interacting policy and norm shifts - F. Stuart Chapin; Elke U. Weber; Elena M. Bennett; Reinette Biggs; Jeroen van den Bergh; W. Neil Adger; Anne-Sophie Crépin; Stephen Polasky; Carl Folke; Marten Scheffer; Kathleen Segerson; John M. Anderies; et al. (Ambio, 2022)
Transformation toward a sustainable future requires an earth stewardship approach to shift society from its current goal of increasing material wealth to a vision of sustaining built, natural, human, and social capital—equitably distributed across society, within and among nations. Widespread concern about earth’s current trajectory and support for actions that would foster more sustainable pathways suggests potential social tipping points in public demand for an earth stewardship vision. Here, we draw on empirical studies and theory to show that movement toward a stewardship vision can be facilitated by changes in either policy incentives or social norms. Our novel contribution is to point out that both norms and incentives must change and can do so interactively. This can be facilitated through leverage points and complementarities across policy areas, based on values, system design, and agency. Potential catalysts include novel democratic institutions and engagement of non-governmental actors, such as businesses, civic leaders, and social movements as agents for redistribution of power. Because no single intervention will transform the world, a key challenge is to align actions to be synergistic, persistent, and scalable.

Corticospinal and peripheral responses to heat-induced hypo-hydration: potential physiological mechanisms and implications for neuromuscular function - Nasir Uddin; Jamie Tallent; Stephen D. Patterson; Stuart Goodall; Mark Waldron (European Journal of Applied Physiology, 2022)
Heat-induced hypo-hydration (hyperosmotic hypovolemia) can reduce prolonged skeletal muscle performance; however, the mechanisms are less well understood and the reported effects on all aspects of neuromuscular function and brief maximal contractions are inconsistent. Historically, a 4–6% reduction of body mass has not been considered to impair muscle function in humans, as determined by muscle torque, membrane excitability and peak power production. With the development of magnetic resonance imaging and neurophysiological techniques, such as electromyography, peripheral nerve, and transcranial magnetic stimulation (TMS), the integrity of the brain-to-muscle pathway can be further investigated. The findings of this review demonstrate that heat-induced hypo-hydration impairs neuromuscular function, particularly during repeated and sustained contractions. Additionally, the mechanisms are separate to those of hyperthermia-induced fatigue and are likely a result of modulations to corticospinal inhibition, increased fibre conduction velocity, pain perception and impaired contractile function. This review also sheds light on the view that hypo-hydration has ‘no effect’ on neuromuscular function during brief maximal voluntary contractions. It is hypothesised that irrespective of unchanged force, compensatory reductions in cortical inhibition are likely to occur, in the attempt of achieving adequate force production. Studies using single-pulse TMS have shown that hypo-hydration can reduce maximal isometric and eccentric force, despite a reduction in cortical inhibition, but the cause of this is currently unclear. Future work should investigate the intracortical inhibitory and excitatory pathways within the brain, to elucidate the role of the central nervous system in force output, following heat-induced hypo-hydration.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Data Quality Influences the Predicted Distribution and Habitat of Four Southern-Hemisphere Albatross Species - Kimberly T. Goetz; Fabrice Stephenson; Andrew Hoskins; Aidan D. Bindoff; Rachael A. Orben; Paul M. Sagar; Leigh G. Torres; Caitlin E. Kroeger; Lisa A. Sztukowski; Richard A. Phillips; Stephen C. Votier; Stuart Bearhop; et al. (Frontiers in Marine Science, 2022)
Few studies have assessed the influence of data quality on the predicted probability of occurrence and preferred habitat of marine predators. We compared results from four species distribution models (SDMs) for four southern-hemisphere albatross species, Buller’s ( Thalassarche bulleri ), Campbell ( T. impavida ), grey-headed ( T. chrysostoma ), and white-capped ( T. steadi ), based on datasets of differing quality, ranging from no location data to twice-daily locations of individual birds collected by geolocation devices. Two relative environmental suitability (RES) models were fit using minimum and maximum preferred and absolute values for each environmental variable based on (1) monthly 50% kernel density contours and background environmental data, and (2) primary literature or expert opinion. Additionally, two boosted regression tree (BRT) models were fit using (1) opportunistic sightings data, and (2) geolocation data from bird-borne electronic tags. Using model-specific threshold values, habitat was quantified for each species and model. Model variables included distance from land, bathymetry, sea surface temperature, and chlorophyll- a concentration. Results from both RES models and the BRT model fit with opportunistic sightings were compared to those from the BRT model fit using geolocation data to assess the influence of data quality on predicted occupancy and habitat. For all species, BRT models outperformed RES models. BRT models offer a predictive advantage over RES models by being able to identify relevant variables, incorporate environmental interactions, and provide spatially explicit estimates of model uncertainty. RES models resulted in larger, less refined areas of predicted habitat for all species. Our study highlights the importance of data quality in predicting the distribution and habitat of albatrosses and emphasises the need to consider the pros and cons associated with different levels of data quality when using SDMs to inform management decisions. Furthermore, we examine the overlap in preferred habitat predicted by each SDM with fishing effort. We discuss the influence of data quality on predicting the wide-scale distributions of pelagic seabirds and how these impacts could result in different protection measures.

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

The effect of dietary (poly)phenols on exercise-induced physiological adaptations: A systematic review and meta-analysis of human intervention trials - Guille Martinez-Negrin; Jarred P. Acton; Stuart P. Cocksedge; Stephen J. Bailey; Tom Clifford (Critical Reviews in Food Science and Nutrition, 2022)

Next‐generation phylogeography resolves post‐glacial colonization patterns in a widespread carnivore, the red fox ( Vulpes vulpes ), in Europe - Allan D. McDevitt; Ilaria Coscia; Samuel S. Browett; Aritz Ruiz‐González; Mark J. Statham; Iwona Ruczyńska; Liam Roberts; Joanna Stojak; Alain C. Frantz; Karin Norén; Erik O. Ågren; Jane Learmount; et al. (Molecular Ecology, 2022)
Carnivores tend to exhibit a lack of (or less pronounced) genetic structure at continental scales in both a geographic and temporal sense and this can confound the identification of post‐glacial colonization patterns in this group. In this study we used genome‐wide data (using genotyping by sequencing [GBS]) to reconstruct the phylogeographic history of a widespread carnivore, the red fox ( Vulpes vulpes ), by investigating broad‐scale patterns of genomic variation, differentiation and admixture amongst contemporary populations in Europe. Using 15,003 single nucleotide polymorphisms (SNPs) from 524 individuals allowed us to identify the importance of refugial regions for the red fox in terms of endemism (e.g., Iberia). In addition, we tested multiple post‐glacial recolonization scenarios of previously glaciated regions during the Last Glacial Maximum using an Approximate Bayesian Computation (ABC) approach that were unresolved from previous studies. This allowed us to identify the role of admixture from multiple source population post‐Younger Dryas in the case of Scandinavia and ancient land‐bridges in the colonization of the British Isles. A natural colonization of Ireland was deemed more likely than an ancient human‐mediated introduction as has previously been proposed and potentially points to a larger mammalian community on the island in the early post‐glacial period. Using genome‐wide data has allowed us to tease apart broad‐scale patterns of structure and diversity in a widespread carnivore in Europe that was not evident from using more limited marker sets and provides a foundation for next‐generation phylogeographic studies in other non‐model species.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Engineered slope failure susceptibility modelling using high spatial resolution geospatial data - Stephen E. Obrike; Stuart L. Barr; Pauline E. Miller; Goodluck K. Anudu (Bulletin of Engineering Geology and the Environment, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Sexual Mismatch Between Vessel-Associated Foraging and Discard Consumption in a Marine Top Predator - Joan Giménez; Gavin E. Arneill; Ashley Bennison; Enrico Pirotta; Hans D. Gerritsen; Thomas W. Bodey; Stuart Bearhop; Keith C. Hamer; Stephen Votier; Mark Jessopp (Frontiers in Marine Science, 2021)
Sex differences in diet and foraging behaviour are common in sexually dimorphic species, often driven by differences in the cost of locomotion or ability to exploit different ecological niches. However, sex-specific foraging strategies also occur in monomorphic or slightly dimorphic species where the drivers are poorly understood. Here, we study sex differences in foraging of northern gannets ( Morus bassanus ), where females are only slightly heavier than males. Using concurrently tracked gannets (298 full foraging trips from 81 individuals) and fishing vessels across 5 years, we quantify individual-based vessel-associated putative foraging, and relate this to discard consumption. We found a significant positive relationship between time spent in vessel-associated foraging and discard consumption for both sexes. However, while females showed greater proportions of vessel-associated foraging than males, discarded fish contributed less to the diet of females in all years. These results contrast with previous suggestions that female gannets interact with vessels less often than males, and are consistent with competitive exclusion of females from trawler-associated discards. Our findings give insight into sexual differences in foraging behaviour in the absence of dimorphism that are necessary to predict their response to environmental and anthropogenic changes.

Our future in the Anthropocene biosphere - Carl Folke; Stephen Polasky; Johan Rockström; Victor Galaz; Frances Westley; Michèle Lamont; Marten Scheffer; Henrik Österblom; Stephen R. Carpenter; F. Stuart Chapin; Karen C. Seto; Elke U. Weber; et al. (Ambio, 2021)
The COVID-19 pandemic has exposed an interconnected and tightly coupled globalized world in rapid change. This article sets the scientific stage for understanding and responding to such change for global sustainability and resilient societies. We provide a systemic overview of the current situation where people and nature are dynamically intertwined and embedded in the biosphere, placing shocks and extreme events as part of this dynamic; humanity has become the major force in shaping the future of the Earth system as a whole; and the scale and pace of the human dimension have caused climate change, rapid loss of biodiversity, growing inequalities, and loss of resilience to deal with uncertainty and surprise. Taken together, human actions are challenging the biosphere foundation for a prosperous development of civilizations. The Anthropocene reality—of rising system-wide turbulence—calls for transformative change towards sustainable futures. Emerging technologies, social innovations, broader shifts in cultural repertoires, as well as a diverse portfolio of active stewardship of human actions in support of a resilient biosphere are highlighted as essential parts of such transformations.

The effect of dietary phytochemicals on nuclear factor erythroid 2-related factor 2 (Nrf2) activation: a systematic review of human intervention trials - Tom Clifford; Jarred P. Acton; Stuart P. Cocksedge; Kelly A. Bowden Davies; Stephen J. Bailey (Molecular Biology Reports, 2021)
We conducted a systematic review of human trials examining the effects of dietary phytochemicals on Nrf2 activation. In accordance with the PRISMA guidelines, Medline, Embase and CAB abstracts were searched for articles from inception until March 2020. Studies in adult humans that measured Nrf2 activation (gene or protein expression changes) following ingestion of a phytochemical, either alone or in combination were included. The study was pre-registered on the Prospero database (Registration Number: CRD42020176121). Twenty-nine full-texts were retrieved and reviewed for analysis; of these, eighteen were included in the systematic review. Most of the included participants were healthy, obese or type 2 diabetics. Study quality was assessed using the Cochrane Collaboration Risk of Bias Assessment tool. Twelve different compounds were examined in the included studies: curcumin, resveratrol and sulforaphane were the most common ( n = 3 each). Approximately half of the studies reported increases in Nrf2 activation ( n = 10); however, many were of poor quality and had an unclear or high risk of bias. There is currently limited evidence that phytochemicals activate Nrf2 in humans. Well controlled human intervention trials are needed to corroborate the findings from in vitro and animal studies.

Calcium signaling: breast cancer’s approach to manipulation of cellular circuitry - Stephen JP Pratt; Erick Hernández-Ochoa; Stuart S Martin (Biophysical Reviews, 2020)
Calcium is a versatile element that participates in cell signaling for a wide range of cell processes such as death, cell cycle, division, migration, invasion, metabolism, differentiation, autophagy, transcription, and others. Specificity of calcium in each of these processes is achieved through modulation of intracellular calcium concentrations by changing the characteristics (amplitude/frequency modulation) or location (spatial modulation) of the signal. Breast cancer utilizes calcium signaling as an advantage for survival and progression. This review integrates evidence showing that increases in expression of calcium channels, GPCRs, pumps, effectors, and enzymes, as well as resulting intracellular calcium signals, lead to high calcium and/or an elevated calcium- mobilizing capacity necessary for malignant functions such as migratory, invasive, proliferative, tumorigenic, or metastatic capacities.

Generation lengths of the world's birds and their implications for extinction risk - Jeremy P. Bird; Robert Martin; H. Reşit Akçakaya; James Gilroy; Ian J. Burfield; Stephen T. Garnett; Andy Symes; Joseph Taylor; Çağan H. Şekercioğlu; Stuart H. M. Butchart (Conservation Biology, 2020)
Birds have been comprehensively assessed on the International Union for Conservation of Nature (IUCN) Red List more times than any other taxonomic group. However, to date, generation lengths have not been systematically estimated to scale population trends when undertaking assessments, as required by the criteria of the IUCN Red List. We compiled information from major databases of published life‐history and trait data for all birds and imputed missing life‐history data as a function of species traits with generalized linear mixed models. Generation lengths were derived for all species, based on our modeled values of age at first breeding, maximum longevity, and annual adult survival. The resulting generation lengths varied from 1.42 to 27.87 years (median 2.99). Most species (61%) had generation lengths

Catalyzing sustainable fisheries management through behavior change interventions - Gavin McDonald; Molly Wilson; Diogo Veríssimo; Rebecca Twohey; Michaela Clemence; Dean Apistar; Stephen Box; Paul Butler; Fel Cesar Cadiz; Stuart J. Campbell; Courtney Cox; Micah Effron; et al. (Conservation Biology, 2020)
Small‐scale fisheries are an important livelihood and primary protein source for coastal communities in many of the poorest regions in the world, yet many are overfished and thus require effective and scalable management solutions. Positive ecological and socioeconomic responses to management typically lag behind immediate costs borne by fishers from fishing pressure reductions necessary for fisheries recovery. These short‐term costs challenge the long‐term success of these interventions. However, social marketing may increase perceptions of management benefits before ecological and socioeconomic benefits are fully realized, driving new social norms and ultimately long‐term sustainable behavior change. By conducting underwater visual surveys to quantify ecological conditions and by conducting household surveys with community members to quantify their perceptions of management support and socioeconomic conditions, we assessed the impact of a standardized small‐scale fisheries management intervention that was implemented across 41 sites in Brazil, Indonesia, and the Philippines. The intervention combines TURF reserves (community‐based territorial use rights for fishing coupled with no‐take marine reserves) with locally tailored social‐marketing behavior change campaigns. Leveraging data across 22 indicators and 4 survey types, along with data from 3 control sites, we found that ecological and socioeconomic impacts varied and that communities supported the intervention and were already changing their fishing practices. These results suggest that communities were developing new social norms and fishing more sustainably before long‐term ecological and socioeconomic benefits of fisheries management materialized.

Using Modern Conservation Tools for Innovative Management of Coral Reefs: The MANACO Consortium - Oliver Selmoni; Gaël Lecellier; Lara Ainley; Antoine Collin; Raimana Doucet; Vaimiti Dubousquet; Hudson Feremaito; Edouard Ito Waia; Stuart Kininmonth; Hélène Magalon; Siola’a Malimali; Ateliana Maugateau; et al. (Frontiers in Marine Science, 2020)

Contemporaneous formation of vein-hosted and stratabound gold mineralization at the world-class Dead Bullock Soak mining camp, Australia - Laura Petrella; Nicolas Thébaud; Crystal LaFlamme; John Miller; Christopher McFarlane; Sandra Occhipinti; Stephen Turner; Stuart Perazzo (Mineralium Deposita, 2020)

Long-term trends in albatross diets in relation to prey availability and breeding success - William F. Mills; José C. Xavier; Stuart Bearhop; Yves Cherel; Stephen C. Votier; Claire M. Waluda; Richard A. Phillips (Marine Biology, 2020)

Testing for changes in biomass dynamics in large‐scale forest datasets - Ervan Rutishauser; Stuart J. Wright; Richard Condit; Stephen P. Hubbell; Stuart J. Davies; Helene C. Muller‐Landau (Global Change Biology, 2020)
Tropical forest responses to climate and atmospheric change are critical to the future of the global carbon budget. Recent studies have reported increases in estimated above‐ground biomass (EAGB) stocks, productivity, and mortality in old‐growth tropical forests. These increases could reflect a shift in forest functioning due to global change and/or long‐lasting recovery from past disturbance. We introduce a novel approach to disentangle the relative contributions of these mechanisms by decomposing changes in whole‐plot biomass fluxes into contributions from changes in the distribution of gap‐successional stages and changes in fluxes for a given stage. Using 30 years of forest dynamic data at Barro Colorado Island, Panama, we investigated temporal variation in EAGB fluxes as a function of initial EAGB (EAGB i ) in 10 × 10 m quadrats. Productivity and mortality fluxes both increased strongly with initial quadrat EAGB. The distribution of EAGB (and thus EAGB i ) across quadrats hardly varied over 30 years (and seven censuses). EAGB fluxes as a function of EAGB i varied largely and significantly among census intervals, with notably higher productivity in 1985–1990 associated with recovery from the 1982–1983 El Niño event. Variation in whole‐plot fluxes among census intervals was explained overwhelmingly by variation in fluxes as a function of EAGB i , with essentially no contribution from changes in EAGB i distributions. The high observed temporal variation in productivity and mortality suggests that this forest is very sensitive to climate variability. There was no consistent long‐term trend in productivity, mortality, or biomass in this forest over 30 years, although the temporal variability in productivity and mortality was so strong that it could well mask a substantial trend. Accurate prediction of future tropical forest carbon budgets will require accounting for disturbance‐recovery dynamics and understanding temporal variability in productivity and mortality.

Fish Diet Shifts Associated with the Northern Gulf of Mexico Hypoxic Zone - Cassandra N. Glaspie; Melissa Clouse; Klaus Huebert; Stuart A. Ludsin; Doran M. Mason; James J. Pierson; Michael R. Roman; Stephen B. Brandt (Estuaries and Coasts, 2019)

SMART Cables for Observing the Global Ocean: Science and Implementation - Bruce M. Howe; Brian K. Arbic; Jérome Aucan; Christopher R. Barnes; Nigel Bayliff; Nathan Becker; Rhett Butler; Laurie Doyle; Shane Elipot; Gregory C. Johnson; Felix Landerer; Stephen Lentz; et al. (Frontiers in Marine Science, 2019)

Four priorities for new links between conservation science and accounting research - Clément Feger; Laurent Mermet; Bhaskar Vira; Prue F.E. Addison; Richard Barker; Frank Birkin; John Burns; Stuart Cooper; Denis Couvet; Thomas Cuckston; Gretchen C. Daily; Colin Dey; et al. (Conservation Biology, 2019)
Article impact statement : New collaborations with accounting research can improve conservation impact of ecosystem‐based information systems.

Simulating the Antarctic stratospheric vortex transport barrier: comparing the Unified Model to reanalysis - Chris Cameron; Gregory E. Bodeker; Jonathan P. Conway; Stephen Stuart; James Renwick (Climate Dynamics, 2019)

Seasonal and Long-Term Dynamics in Stream Water Sodium Chloride Concentrations and the Effectiveness of Road Salt Best Management Practices - Victoria R. Kelly; Stuart E. Findlay; Stephen K. Hamilton; Gary M. Lovett; Kathleen C. Weathers (Water, Air, & Soil Pollution, 2019)

Pulsatile interaction between the macro-vasculature and micro-vasculature: proof-of-concept among patients with type 2 diabetes - Rachel E. D. Climie; Dean S. Picone; Sarah Blackwood; Stuart E. Keel; Ahmad Qasem; Stephen Rattigan; James E. Sharman (European Journal of Applied Physiology, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Progress in designing and delivering effective fishing industry–science data collection in the UK - Stephen C Mangi; Sven Kupschus; Steven Mackinson; Dale Rodmell; Alexandra Lee; Elizabeth Bourke; Tom Rossiter; Jim Masters; Stuart Hetherington; Thomas Catchpole; David Righton (Fish and Fisheries, 2018)
This study was undertaken to address the increasing need for a strategic approach to industry–science data collections in the face of reducing resources and growing need for evidence in fisheries management. The aim was to evaluate progress in the development of plans and procedures that can be employed to collect, record and use fishing industry knowledge and data in the evidence base for managing fisheries. This was achieved by reviewing industry‐led data initiatives already undertaken or ongoing within the United Kingdom to document how these projects have/are incorporating fishing industry data into the process of management decision‐making; canvassing stakeholder opinion on data gaps and whether these could be filled by data gathered by commercial fishing vessels; establishing what issues might prevent or stimulate commercial fishing vessels in collecting data when they have the opportunity; and describing guidance on a step‐by‐step process for gathering scientific information such that fishers are empowered to collect the right data, at the right times and in the right format for their fishery. Given recent advances in the collection, interpretation and application of fisheries‐dependent data, we compare progress made in the UK to other areas of the world. We conclude that there is considerable evidence of a paradigm shift from the conventional practice of scientists asking fishers to provide data for scientific analyses towards full engagement of key stakeholders in data collection.

Clarifying the key biodiversity areas partnership and programme - Simon N. Stuart; Thomas M. Brooks; Stuart H. M. Butchart; Wendy Elliott; Melanie Heath; Dieter Hoffmann; Leslie Honey; Irina Kostadinova; Penny Langhammer; Olivier Langrand; Susan Lieberman; Daniel Marnewick; et al. (Biodiversity and Conservation, 2018)

Author Correction to: Size-mediated control of perch–midge coupling in Lake Erie transient dead zones - Daisuke Goto; James J. Roberts; Steven A. Pothoven; Stuart A. Ludsin; Henry A. Vanderploeg; Stephen B. Brandt; Tomas O. Höök (Environmental Biology of Fishes, 2017)

Size-mediated control of perch–midge coupling in Lake Erie transient dead zones - Daisuke Goto; James J. Roberts; Steven A. Pothoven; Stuart A. Ludsin; Henry A. Vanderploeg; Stephen B. Brandt; Tomas O. Höök (Environmental Biology of Fishes, 2017)

A case for redefining the boundaries of the Mesoamerican Reef Ecoregion - Iliana Chollett; Lysel Garavelli; Daniel Holstein; Laurent Cherubin; Stuart Fulton; Stephen J. Box (Coral Reefs, 2017)

Variations of leaf longevity in tropical moist forests predicted by a trait‐driven carbon optimality model - Xiangtao Xu; David Medvigy; Stuart Joseph Wright; Kaoru Kitajima; Jin Wu; Loren P. Albert; Giordane A. Martins; Scott R. Saleska; Stephen W. Pacala (Ecology Letters, 2017)
Leaf longevity ( LL ) varies more than 20‐fold in tropical evergreen forests, but it remains unclear how to capture these variations using predictive models. Current theories of LL that are based on carbon optimisation principles are challenging to quantitatively assess because of uncertainty across species in the ‘ageing rate:’ the rate at which leaf photosynthetic capacity declines with age. Here, we present a meta‐analysis of 49 species across temperate and tropical biomes, demonstrating that the ageing rate of photosynthetic capacity is positively correlated with the mass‐based carboxylation rate of mature leaves. We assess an improved trait‐driven carbon optimality model with in situ LL data for 105 species in two Panamanian forests. We show that our model explains over 40% of the cross‐species variation in LL under contrasting light environment. Collectively, our results reveal how variation in LL emerges from carbon optimisation constrained by both leaf structural traits and abiotic environment.

Contrasting outcomes of species‐ and community‐level analyses of the temporal consistency of functional composition - Masatoshi Katabuchi; S. Joseph Wright; Nathan G. Swenson; Kenneth J. Feeley; Richard Condit; Stephen P. Hubbell; Stuart J. Davies (Ecology, 2017)
Multiple anthropogenic drivers affect every natural community, and there is broad interest in using functional traits to understand and predict the consequences for future biodiversity. There is, however, no consensus regarding the choice of analytical methods. We contrast species‐ and community‐level analyses of change in the functional composition for four traits related to drought tolerance using three decades of repeat censuses of trees in the 50‐ha Forest Dynamics Plot on Barro Colorado Island, Panama. Community trait distributions shifted significantly through time, which may indicate a shift toward more drought tolerant species. However, at the species level, changes in abundance were unrelated to trait values. To reconcile these seemingly contrasting results, we evaluated species‐specific contributions to the directional shifts observed at the community level. Abundance changes of just one to six of 312 species were responsible for the community‐level shifts observed for each trait. Our results demonstrate that directional changes in community‐level functional composition can result from idiosyncratic change in a few species rather than widespread community‐wide changes associated with functional traits. Future analyses of directional change in natural communities should combine community‐, species‐, and possibly individual‐level analyses to uncover relationships with function that can improve understanding and enable prediction.

The Influence of Hydrologic Residence Time on Lake Carbon Cycling Dynamics Following Extreme Precipitation Events - Jacob A. Zwart; Stephen D. Sebestyen; Christopher T. Solomon; Stuart E. Jones (Ecosystems, 2017)

Stable isotopes and mtDNA reveal niche segregation but no evidence of intergradation along a habitat gradient in the Lesser Whitethroat complex (Sylvia curruca; Passeriformes; Aves) - Stephen C. Votier; Simon Aspinall; Stuart Bearhop; David Bilton; Jason Newton; Per Alström; Paul Leader; Geoff Carey; Robert W. Furnes; Urban Olsson (Journal of Ornithology, 2016)

Choice of baseline climate data impacts projected species' responses to climate change - David J. Baker; Andrew J. Hartley; Stuart H. M. Butchart; Stephen G. Willis (Global Change Biology, 2016)
Climate data created from historic climate observations are integral to most assessments of potential climate change impacts, and frequently comprise the baseline period used to infer species‐climate relationships. They are often also central to downscaling coarse resolution climate simulations from General Circulation Models ( GCM s) to project future climate scenarios at ecologically relevant spatial scales. Uncertainty in these baseline data can be large, particularly where weather observations are sparse and climate dynamics are complex (e.g. over mountainous or coastal regions). Yet, importantly, this uncertainty is almost universally overlooked when assessing potential responses of species to climate change. Here, we assessed the importance of historic baseline climate uncertainty for projections of species' responses to future climate change. We built species distribution models ( SDM s) for 895 African bird species of conservation concern, using six different climate baselines. We projected these models to two future periods (2040–2069, 2070–2099), using downscaled climate projections, and calculated species turnover and changes in species‐specific climate suitability. We found that the choice of baseline climate data constituted an important source of uncertainty in projections of both species turnover and species‐specific climate suitability, often comparable with, or more important than, uncertainty arising from the choice of GCM . Importantly, the relative contribution of these factors to projection uncertainty varied spatially. Moreover, when projecting SDM s to sites of biodiversity importance (Important Bird and Biodiversity Areas), these uncertainties altered site‐level impacts, which could affect conservation prioritization. Our results highlight that projections of species' responses to climate change are sensitive to uncertainty in the baseline climatology. We recommend that this should be considered routinely in such analyses.

Quantifying the relative irreplaceability of important bird and biodiversity areas - Moreno Di Marco; Thomas Brooks; Annabelle Cuttelod; Lincoln D.C. Fishpool; Carlo Rondinini; Robert J. Smith; Leon Bennun; Stuart H.M. Butchart; Simon Ferrier; Ruud P.B. Foppen; Lucas Joppa; Diego Juffe‐Bignoli; et al. (Conservation Biology, 2016)
World governments have committed to increase the global protected areas coverage by 2020, but the effectiveness of this commitment for protecting biodiversity depends on where new protected areas are located. Threshold‐ and complementarity‐based approaches have been independently used to identify important sites for biodiversity. We brought together these approaches by performing a complementarity‐based analysis of irreplaceability in important bird and biodiversity areas (IBAs), which are sites identified using a threshold‐based approach. We determined whether irreplaceability values are higher inside than outside IBAs and whether any observed difference depends on known characteristics of the IBAs. We focused on 3 regions with comprehensive IBA inventories and bird distribution atlases: Australia, southern Africa, and Europe. Irreplaceability values were significantly higher inside than outside IBAs, although differences were much smaller in Europe than elsewhere. Higher irreplaceability values in IBAs were associated with the presence and number of restricted‐range species; number of criteria under which the site was identified; and mean geographic range size of the species for which the site was identified (trigger species). In addition, IBAs were characterized by higher irreplaceability values when using proportional species representation targets, rather than fixed targets. There were broadly comparable results when measuring irreplaceability for trigger species and when considering all bird species, which indicates a good surrogacy effect of the former. Recently, the International Union for Conservation of Nature has convened a consultation to consolidate global standards for the identification of key biodiversity areas (KBAs), building from existing approaches such as IBAs. Our results informed this consultation, and in particular a proposed irreplaceability criterion that will allow the new KBA standard to draw on the strengths of both threshold‐ and complementarity‐based approaches.

Genotypic variation in foundation species generates network structure that may drive community dynamics and evolution - Matthew K. Lau; Arthur R. Keith; Stuart R. Borrett; Stephen M. Shuster; Thomas G. Whitham (Ecology, 2016)
Although genetics in a single species is known to impact whole communities, little is known about how genetic variation influences species interaction networks in complex ecosystems. Here, we examine the interactions in a community of arthropod species on replicated genotypes (clones) of a foundation tree species, Populus angustifolia James (narrowleaf cottonwood), in a long‐term, common garden experiment using a bipartite “genotype–species” network perspective. We combine this empirical work with a simulation experiment designed to further investigate how variation among individual tree genotypes can impact network structure. Three findings emerged: (1) the empirical “genotype–species network” exhibited significant network structure with modularity being greater than the highly conservative null model; (2) as would be expected given a modular network structure, the empirical network displayed significant positive arthropod co‐occurrence patterns; and (3) furthermore, the simulations of “genotype–species” networks displayed variation in network structure, with modularity in particular clearly increasing, as genotypic variation increased. These results support the conclusion that genetic variation in a single species contributes to the structure of ecological interaction networks, which could influence ecological dynamics (e.g., assembly and stability) and evolution in a community context.

Relating belowground microbial composition to the taxonomic, phylogenetic, and functional trait distributions of trees in a tropical forest - Albert Barberán; Krista L. McGuire; Jeffrey A. Wolf; F. Andrew Jones; Stuart Joseph Wright; Benjamin L. Turner; Adam Essene; Stephen P. Hubbell; Brant C. Faircloth; Noah Fierer (Ecology Letters, 2015)
The complexities of the relationships between plant and soil microbial communities remain unresolved. We determined the associations between plant aboveground and belowground (root) distributions and the communities of soil fungi and bacteria found across a diverse tropical forest plot. Soil microbial community composition was correlated with the taxonomic and phylogenetic structure of the aboveground plant assemblages even after controlling for differences in soil characteristics, but these relationships were stronger for fungi than for bacteria. In contrast to expectations, the species composition of roots in our soil core samples was a poor predictor of microbial community composition perhaps due to the patchy, ephemeral, and highly overlapping nature of fine root distributions. Our ability to predict soil microbial composition was not improved by incorporating information on plant functional traits suggesting that the most commonly measured plant traits are not particularly useful for predicting the plot‐level variability in belowground microbial communities.

Long‐term individual foraging site fidelity—why some gannets don't change their spots - Ewan D. Wakefield; Ian R. Cleasby; Stuart Bearhop; Thomas W. Bodey; Rachel D. Davies; Peter I. Miller; Jason Newton; Stephen C. Votier; Keith C. Hamer (Ecology, 2015)
Many established models of animal foraging assume that individuals are ecologically equivalent. However, it is increasingly recognized that populations may comprise individuals who differ consistently in their diets and foraging behaviors. For example, recent studies have shown that individual foraging site fidelity (IFSF, when individuals consistently forage in only a small part of their population's home range) occurs in some colonial breeders. Short‐term IFSF could result from animals using a win–stay, lose–shift foraging strategy. Alternatively, it may be a consequence of individual specialization. Pelagic seabirds are colonial central‐place foragers, classically assumed to use flexible foraging strategies to target widely dispersed, spatiotemporally patchy prey. However, tracking has shown that IFSF occurs in many seabirds, although it is not known whether this persists across years. To test for long‐term IFSF and to examine alternative hypotheses concerning its cause, we repeatedly tracked 55 Northern Gannets ( Morus bassanus ) from a large colony in the North Sea within and across three successive breeding seasons. Gannets foraged in neritic waters, predictably structured by tidal mixing and thermal stratification, but subject to stochastic, wind‐induced overturning. Both within and across years, coarse to mesoscale (tens of kilometers) IFSF was significant but not absolute, and foraging birds departed the colony in individually consistent directions. Carbon stable isotope ratios in gannet blood tissues were repeatable within years and nitrogen ratios were also repeatable across years, suggesting long‐term individual dietary specialization. Individuals were also consistent across years in habitat use with respect to relative sea surface temperature and in some dive metrics, yet none of these factors accounted for IFSF. Moreover, at the scale of weeks, IFSF did not decay over time and the magnitude of IFSF across years was similar to that within years, suggesting that IFSF is not primarily the result of win–stay, lose–shift foraging. Rather, we hypothesize that site familiarity, accrued early in life, causes IFSF by canalizing subsequent foraging decisions. Evidence from this and other studies suggests that IFSF may be common in colonial central‐place foragers, with far‐reaching consequences for our attempts to understand and conserve these animals in a rapidly changing environment.

Estimating the normal background rate of species extinction - Jurriaan M. De Vos; Lucas N. Joppa; John L. Gittleman; Patrick R. Stephens; Stuart L. Pimm (Conservation Biology, 2015)
A key measure of humanity's global impact is by how much it has increased species extinction rates. Familiar statements are that these are 100–1000 times pre‐human or background extinction levels. Estimating recent rates is straightforward, but establishing a background rate for comparison is not. Previous researchers chose an approximate benchmark of 1 extinction per million species per year (E/MSY). We explored disparate lines of evidence that suggest a substantially lower estimate. Fossil data yield direct estimates of extinction rates, but they are temporally coarse, mostly limited to marine hard‐bodied taxa, and generally involve genera not species. Based on these data, typical background loss is 0.01 genera per million genera per year. Molecular phylogenies are available for more taxa and ecosystems, but it is debated whether they can be used to estimate separately speciation and extinction rates. We selected data to address known concerns and used them to determine median extinction estimates from statistical distributions of probable values for terrestrial plants and animals. We then created simulations to explore effects of violating model assumptions. Finally, we compiled estimates of diversification—the difference between speciation and extinction rates for different taxa. Median estimates of extinction rates ranged from 0.023 to 0.135 E/MSY. Simulation results suggested over‐ and under‐estimation of extinction from individual phylogenies partially canceled each other out when large sets of phylogenies were analyzed. There was no evidence for recent and widespread pre‐human overall declines in diversity. This implies that average extinction rates are less than average diversification rates. Median diversification rates were 0.05–0.2 new species per million species per year. On the basis of these results, we concluded that typical rates of background extinction may be closer to 0.1 E/MSY. Thus, current extinction rates are 1,000 times higher than natural background rates of extinction and future rates are likely to be 10,000 times higher. Estimación de la Tasa Normal de Extinción de Especies

Evaluating the relative conservation value of fully and partially protected marine areas - Marija Sciberras; Stuart R Jenkins; Rebecca Mant; Michel J Kaiser; Stephen J Hawkins; Andrew S Pullin (Fish and Fisheries, 2015)
The establishment of marine protected areas ( MPA s), particularly of no‐take areas, is often viewed as a conflict between conservation and fishing. Partially protected areas ( PPA s) that restrict some extractive uses are often regarded as a balance between biodiversity conservation and socio‐economic viability. Few attempts have been made to generalize the ecological effects of PPA s. We synthesized the results of empirical studies that compared PPA s to (i) no‐take reserves ( NTR s) and (ii) to open access ( O pen) areas, to assess the potential benefits of different levels of protection for fish populations. Response to protection was examined in relation to MPA parameters and the exploitation status of fish. Our syntheses suggest that while PPA s significantly enhance density and biomass of fish relative to O pen areas, NTR s yielded significantly higher biomass of fish within their boundaries relative to PPA s. The positive response to protection was primarily driven by target species. There was a large degree of variability in the magnitude of response to protection, although the size of the PPA explained some of this variability. The protection regime within the PPA provided useful insights into the effectiveness of partial MPA s. We conclude that MPA s with partial protection confer advantages, such as enhanced density and biomass of fish, compared to areas with no restrictions, although the strongest responses occurred for areas with total exclusion. Thus, MPA s with a combination of protection levels are a valuable spatial management tool particularly in areas where exclusion of all activities is not a socio‐economically and politically viable option.

Does flood rhythm drive ecosystem responses in tropical riverscapes? - Timothy D. Jardine; Nicholas R. Bond; Michele A. Burford; Mark J. Kennard; Douglas P. Ward; Peter Bayliss; Peter M. Davies; Michael M. Douglas; Stephen K. Hamilton; John M. Melack; Robert J. Naiman; Neil E. Pettit; et al. (Ecology, 2015)
Biotic communities are shaped by adaptations from generations of exposure to selective pressures by recurrent and often infrequent events. In large rivers, floods can act as significant agents of change, causing considerable physical and biotic disturbance while often enhancing productivity and diversity. We show that the relative balance between these seemingly divergent outcomes can be explained by the rhythmicity, or predictability of the timing and magnitude, of flood events. By analyzing biological data for large rivers that span a gradient of rhythmicity in the Neotropics and tropical Australia, we find that systems with rhythmic annual floods have higher fish species richness, more stable avian populations, and elevated rates of riparian forest production compared with those with arrhythmic flood pulses. Intensification of the hydrological cycle driven by climate change, coupled with reductions in runoff due to water extractions for human use and altered discharge from impoundments, is expected to alter the hydrologic rhythmicity of floodplain rivers with significant consequences for both biodiversity and productivity.

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Potential impact of invasive alien species on ecosystem services provided by a tropical forested ecosystem: a case study from Montserrat - Kelvin S.-H. Peh; Andrew Balmford; Jennifer C. Birch; Claire Brown; Stuart H. M. Butchart; James Daley; Jeffrey Dawson; Gerard Gray; Francine M. R. Hughes; Stephen Mendes; James Millett; Alison J. Stattersfield; et al. (Biological Invasions, 2015)

Phenotypic variation in shell form in the intertidal acorn barnacle Chthamalus montagui: distribution, response to predators and life history trade-offs - Jefferson Murua; Michael T. Burrows; Roger N. Hughes; Stephen J. Hawkins; Richard C. Thompson; Stuart R. Jenkins (Marine Biology, 2014)

An assessment of endocrine activity in Australian rivers using chemical and in vitro analyses - Philip D. Scott; Michael Bartkow; Stephen J. Blockwell; Heather M. Coleman; Stuart J. Khan; Richard Lim; James A. McDonald; Helen Nice; Dayanthi Nugegoda; Vincent Pettigrove; Louis A. Tremblay; Michael St. J. Warne; et al. (Environmental Science and Pollution Research, 2014)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Small Molecule Specific Run Acceptance, Specific Assay Operation, and Chromatographic Run Quality Assessment: Recommendation for Best Practices and Harmonization from the Global Bioanalysis Consortium Harmonization Teams - Eric J. Woolf; Stuart McDougall; Douglas M. Fast; Maristela Andraus; Matthew Barfield; Michael Blackburn; Ben Gordon; David Hoffman; Noriko Inoue; Gabriel Marcelin-Jimenez; Amy Flynn; Richard LeLacheur; et al. (The AAPS Journal, 2014)

Temporal variability of forest communities: empirical estimates of population change in 4000 tree species - Ryan A. Chisholm; Richard Condit; K. Abd. Rahman; Patrick J. Baker; Sarayudh Bunyavejchewin; Yu‐Yun Chen; George Chuyong; H. S. Dattaraja; Stuart Davies; Corneille E. N. Ewango; C. V. S. Gunatilleke; I. A. U. Nimal Gunatilleke; et al. (Ecology Letters, 2014)
Long‐term surveys of entire communities of species are needed to measure fluctuations in natural populations and elucidate the mechanisms driving population dynamics and community assembly. We analysed changes in abundance of over 4000 tree species in 12 forests across the world over periods of 6–28 years. Abundance fluctuations in all forests are large and consistent with population dynamics models in which temporal environmental variance plays a central role. At some sites we identify clear environmental drivers, such as fire and drought, that could underlie these patterns, but at other sites there is a need for further research to identify drivers. In addition, cross‐site comparisons showed that abundance fluctuations were smaller at species‐rich sites, consistent with the idea that stable environmental conditions promote higher diversity. Much community ecology theory emphasises demographic variance and niche stabilisation; we encourage the development of theory in which temporal environmental variance plays a central role.

A taxonomic comparison of local habitat niches of tropical trees - Claire A. Baldeck; Steven W. Kembel; Kyle E. Harms; Joseph B. Yavitt; Robert John; Benjamin L. Turner; George B. Chuyong; David Kenfack; Duncan W. Thomas; Sumedha Madawala; Nimal Gunatilleke; Savitri Gunatilleke; et al. (Oecologia, 2013)

Evaluating the effectiveness of conservation site networks under climate change: accounting for uncertainty - Robert Bagchi; Mike Crosby; Brian Huntley; David G. Hole; Stuart H. M. Butchart; Yvonne Collingham; Mohit Kalra; Jagadish Rajkumar; Asad Rahmani; Mitra Pandey; Hum Gurung; Le Trong Trai; et al. (Global Change Biology, 2013)
We forecasted potential impacts of climate change on the ability of a network of key sites for bird conservation (Important Bird Areas; IBA s) to provide suitable climate for 370 bird species of current conservation concern in two Asian biodiversity hotspots: the Eastern Himalaya and Lower Mekong. Comparable studies have largely not accounted for uncertainty, which may lead to inappropriate conclusions. We quantified the contribution of four sources of variation (choice of general circulation models, emission scenarios and species distribution modelling methods and variation in species distribution data) to uncertainty in forecasts and tested if our projections were robust to these uncertainties. Declines in the availability of suitable climate within the IBA network by 2100 were forecast as ‘extremely likely’ for 45% of species, whereas increases were projected for only 2%. Thus, we predict almost 24 times as many ‘losers’ as ‘winners’. However, for no species was suitable climate ‘extremely likely’ to be completely lost from the network. Considerable turnover (median = 43%, 95% CI = 35–69%) in species compositions of most IBA s were projected by 2100. Climatic conditions in 47% of IBA s were projected as ‘extremely likely’ to become suitable for fewer priority species. However, no IBA was forecast to become suitable for more species. Variation among General Circulation Models and Species Distribution Models contributed most to uncertainty among forecasts. This uncertainty precluded firm conclusions for 53% of species and IBA s because 95% confidence intervals included projections of no change. Considering this uncertainty, however, allows robust recommendations concerning the remaining species and IBA s. Overall, while the IBA network will continue to sustain bird conservation, climate change will modify which species each site will be suitable for. Thus, adaptive management of the network, including modified site conservation strategies and facilitating species' movement among sites, is critical to ensure effective future conservation.

Denning behaviour of the European badger (Meles meles) correlates with bovine tuberculosis infection status - Nicola Weber; Stuart Bearhop; Sasha R. X. Dall; Richard J. Delahay; Robbie A. McDonald; Stephen P. Carter (Behavioral Ecology and Sociobiology, 2013)

Towards an integrated global framework to assess the impacts of land use and management change on soil carbon: current capability and future vision - Pete Smith; Christian A. Davies; Stephen Ogle; Giuliana Zanchi; Jessica Bellarby; Neil Bird; Robert M. Boddey; Niall P. McNamara; David Powlson; Annette Cowie; Meine van Noordwijk; Sarah C. Davis; et al. (Global Change Biology, 2012)
I ntergovernmental P anel on C limate C hange ( IPCC ) T ier 1 methodologies commonly underpin project‐scale carbon accounting for changes in land use and management and are used in frameworks for L ife C ycle A ssessment and carbon footprinting of food and energy crops. These methodologies were intended for use at large spatial scales. This can introduce error in predictions at finer spatial scales. There is an urgent need for development and implementation of higher tier methodologies that can be applied at fine spatial scales (e.g. farm/project/plantation) for food and bioenergy crop greenhouse gas (GHG) accounting to facilitate decision making in the land‐based sectors. Higher tier methods have been defined by IPCC and must be well evaluated and operate across a range of domains (e.g. climate region, soil type, crop type, topography), and must account for land use transitions and management changes being implemented. Furthermore, the data required to calibrate and drive the models used at higher tiers need to be available and applicable at fine spatial resolution, covering the meteorological, soil, cropping system and management domains, with quantified uncertainties. Testing the reliability of the models will require data either from sites with repeated measurements or from chronosequences. We review current global capability for estimating changes in soil carbon at fine spatial scales and present a vision for a framework capable of quantifying land use change and management impacts on soil carbon, which could be used for addressing issues such as bioenergy and biofuel sustainability, food security, forest protection, and direct/indirect impacts of land use change. The aim of this framework is to provide a globally accepted standard of carbon measurement and modelling appropriate for GHG accounting that could be applied at project to national scales (allowing outputs to be scaled up to a country level), to address the impacts of land use and land management change on soil carbon.

Altered Lung Motion is a Sensitive Indicator of Regional Lung Disease - Andreas Fouras; Beth J. Allison; Marcus J. Kitchen; Stephen Dubsky; Jayne Nguyen; Kerry Hourigan; Karen K. W. Siu; Rob A. Lewis; Megan J. Wallace; Stuart B. Hooper (Annals of Biomedical Engineering, 2012)

Population trends in the Slavonian grebe Podiceps auritus (L.) and Chironomidae (Diptera) at a Scottish loch - Stephen J. Brooks; Vivienne J. Jones; Richard J. Telford; Peter G. Appleby; Emily Watson; Suzanne McGowan; Stuart Benn (Journal of Paleolimnology, 2012)

Fish mediate high food web connectivity in the lower reaches of a tropical floodplain river - Timothy D. Jardine; Bradley J. Pusey; Stephen K. Hamilton; Neil E. Pettit; Peter M. Davies; Michael M. Douglas; Vivian Sinnamon; Ian A. Halliday; Stuart E. Bunn (Oecologia, 2012)

Downscaling and visioning of mountain snow packs and other climate change implications in North Vancouver, British Columbia - Stewart Jay Cohen; Stephen Sheppard; Alison Shaw; David Flanders; Sarah Burch; Bill Taylor; David Hutchinson; Alex Cannon; Stuart Hamilton; Brent Burton; Jeff Carmichael (Mitigation and Adaptation Strategies for Global Change, 2012)

Reconnecting to the Biosphere - Carl Folke; Åsa Jansson; Johan Rockström; Per Olsson; Stephen R. Carpenter; F. Stuart Chapin; Anne-Sophie Crépin; Gretchen Daily; Kjell Danell; Jonas Ebbesson; Thomas Elmqvist; Victor Galaz; et al. (Ambio, 2011)

Physiological consequences of military high-speed boat transits - Stephen D. Myers; Trevor D. Dobbins; Stuart King; Benjamin Hall; Ruth M. Ayling; Sharon R. Holmes; Tom Gunston; Rosemary Dyson (European Journal of Applied Physiology, 2011)

Toward a Management Framework for Networks of Protected Areas in the Face of Climate Change - DAVID G. HOLE; BRIAN HUNTLEY; JULIUS ARINAITWE; STUART H. M. BUTCHART; YVONNE C. COLLINGHAM; LINCOLN D. C. FISHPOOL; DEBORAH J. PAIN; STEPHEN G. WILLIS (Conservation Biology, 2011)
Networks of sites of high importance for conservation of biological diversity are a cornerstone of current conservation strategies but are fixed in space and time. As climate change progresses, substantial shifts in species’ ranges may transform the ecological community that can be supported at a given site. Thus, some species in an existing network may not be protected in the future or may be protected only if they can move to sites that in future provide suitable conditions. We developed an approach to determine appropriate climate‐change adaptation strategies for individual sites within a network that was based on projections of future changes in the relative proportions of emigrants (species for which a site becomes climatically unsuitable), colonists (species for which a site becomes climatically suitable), and persistent species (species able to remain within a site despite the climatic change). Our approach also identifies key regions where additions to a network could enhance its future effectiveness. Using the sub‐Saharan African Important Bird Area (IBA) network as a case study, we found that appropriate conservation strategies for individual sites varied widely across sub‐Saharan Africa, and key regions where new sites could help increase network robustness varied in space and time. Although these results highlight the potential difficulties within any planning framework that seeks to address climate‐change adaptation needs, they demonstrate that such planning frameworks are necessary, if current conservation strategies are to be adapted effectively, and feasible, if applied judiciously.

NIR Spectroscopy Applications in the Development of a Compacted Multiparticulate System for Modified Release - Stuart L. Cantor; Stephen W. Hoag; Christopher D. Ellison; Mansoor A. Khan; Robbe C. Lyon (AAPS PharmSciTech, 2011)

Functional traits and the growth–mortality trade‐off in tropical trees - S. Joseph Wright; Kaoru Kitajima; Nathan J. B. Kraft; Peter B. Reich; Ian J. Wright; Daniel E. Bunker; Richard Condit; James W. Dalling; Stuart J. Davies; Sandra Díaz; Bettina M. J. Engelbrecht; Kyle E. Harms; et al. (Ecology, 2010)
A trade‐off between growth and mortality rates characterizes tree species in closed canopy forests. This trade‐off is maintained by inherent differences among species and spatial variation in light availability caused by canopy‐opening disturbances. We evaluated conditions under which the trade‐off is expressed and relationships with four key functional traits for 103 tree species from Barro Colorado Island, Panama. The trade‐off is strongest for saplings for growth rates of the fastest growing individuals and mortality rates of the slowest growing individuals ( r 2 = 0.69), intermediate for saplings for average growth rates and overall mortality rates ( r 2 = 0.46), and much weaker for large trees ( r 2 ≤ 0.10). This parallels likely levels of spatial variation in light availability, which is greatest for fast‐ vs. slow‐growing saplings and least for large trees with foliage in the forest canopy. Inherent attributes of species contributing to the trade‐off include abilities to disperse, acquire resources, grow rapidly, and tolerate shade and other stresses. There is growing interest in the possibility that functional traits might provide insight into such ecological differences and a growing consensus that seed mass (SM), leaf mass per area (LMA), wood density (WD), and maximum height ( H max ) are key traits among forest trees. Seed mass, LMA, WD, and H max are predicted to be small for light‐demanding species with rapid growth and mortality and large for shade‐tolerant species with slow growth and mortality. Six of these trait–demographic rate predictions were realized for saplings; however, with the exception of WD, the relationships were weak ( r 2 r 2 80% of the explained variation and, after WD was included, LMA and H max made insignificant contributions. Virtually the full range of values of SM, LMA, and H max occurred at all positions on the growth–mortality trade‐off. Although WD provides a promising start, a successful trait‐based ecology of tropical forest trees will require consideration of additional traits.

Combining plant resistance and a natural enemy to control Amphorophora idaei - Carolyn Mitchell; Scott N. Johnson; Stuart C. Gordon; A. Nicholas E. Birch; Stephen F. Hubbard (BioControl, 2010)

Determinants of reproductive potential and population size in open populations of Patella vulgata - Andreas Sundelöf; Stuart R. Jenkins; Carl J. Svensson; Jane Delany; Stephen J. Hawkins; Per Åberg (Marine Biology, 2010)

Papyriferic Acid, An Antifeedant Triterpene From Birch Trees, Inhibits Succinate Dehydrogenase From Liver Mitochondria - Stuart McLean; Stephen M. Richards; Siow-Leng Cover; Sue Brandon; Noel W. Davies; John P. Bryant; Thomas P. Clausen (Journal of Chemical Ecology, 2009)

Nitrate removal in stream ecosystems measured by 15N addition experiments: Denitrification - Patrick J. Mulholland; Robert O. Hall; Daniel J. Sobota; Walter K. Dodds; Stuart E. G. Findlay; Nancy B. Grimm; Stephen K. Hamilton; William H. McDowell; Jonathan M. O'Brien; Jennifer L. Tank; Linda R. Ashkenas; Lee W. Cooper; et al. (Limnology and Oceanography, 2009)
We measured denitrification rates using a field 15 NO 3 − tracer‐addition approach in a large, cross‐site study of nitrate uptake in reference, agricultural, and suburban‐urban streams. We measured denitrification rates in 49 of 72 streams studied. Uptake length due to denitrification ( S Wden n) ranged from 89 m to 184 km (median of 9050 m) and there were no significant differences among regions or land‐use categories, likely because of the wide range of conditions within each region and land use. N 2 production rates far exceeded N 2 O production rates in all streams. The fraction of total NO 3 − removal from water due to denitrification ranged from 0.5% to 100% among streams (median of 16%), and was related to NH 4 + concentration and ecosystem respiration rate (ER). Multivariate approaches showed that the most important factors controlling S Wden were specific discharge (discharge / width) and NO 3 − concentration (positive effects), and ER and transient storage zones (negative effects). The relationship between areal denitrification rate ( U den ) and NO 3 − concentration indicated a partial saturation effect. A power function with an exponent of 0.5 described this relationship better than a Michaelis‐Menten equation. Although U den increased with increasing NO 3 − concentration, the efficiency of NO 3 − removal from water via denitrification declined, resulting in a smaller proportion of streamwater NO 3 − load removed over a given length of stream. Regional differences in stream denitrification rates were small relative to the proximate factors of NO 3 − concentration and ecosystem respiration rate, and land use was an important but indirect control on denitrification in streams, primarily via its effect on NO 3 − concentration.

Projected impacts of climate change on a continent‐wide protected area network - David G. Hole; Stephen G. Willis; Deborah J. Pain; Lincoln D. Fishpool; Stuart H. M. Butchart; Yvonne C. Collingham; Carsten Rahbek; Brian Huntley (Ecology Letters, 2009)
Despite widespread concern, the continuing effectiveness of networks of protected areas under projected 21st century climate change is uncertain. Shifts in species’ distributions could mean these resources will cease to afford protection to those species for which they were originally established. Using modelled projected shifts in the distributions of sub‐Saharan Africa’s entire breeding avifauna, we show that species turnover across the continent’s Important Bird Area (IBA) network is likely to vary regionally and will be substantial at many sites (> 50% at 42% of IBAs by 2085 for priority species). Persistence of suitable climate space across the network as a whole, however, is notably high, with 88–92% of priority species retaining suitable climate space in ≥ 1 IBA(s) in which they are currently found. Only 7–8 priority species lose climatic representation from the network. Hence, despite the likelihood of significant community disruption, we demonstrate that rigorously defined networks of protected areas can play a key role in mitigating the worst impacts of climate change on biodiversity.

Identification of Sex Pheromone Components of the Hessian Fly, Mayetiola destructor - Martin N. Andersson; Jenny Haftmann; Jeffrey J. Stuart; Sue E. Cambron; Marion O. Harris; Stephen P. Foster; Stephan Franke; Wittko Francke; Ylva Hillbur (Journal of Chemical Ecology, 2009)

An ultrasound investigation into the morphology of the human abdominal wall uncovers complex deformation patterns during contraction - Stephen H. M. Brown; Stuart M. McGill (European Journal of Applied Physiology, 2008)

COMPARATIVE ECOLOGY OF NORTH ATLANTIC SHORES: DO DIFFERENCES IN PLAYERS MATTER FOR PROCESS? - Stuart R. Jenkins; Pippa Moore; Michael T. Burrows; David J. Garbary; Stephen J. Hawkins; Agnar Ingólfsson; Kenneth P. Sebens; Paul V. R. Snelgrove; David S. Wethey; Sarah A. Woodin (Ecology, 2008)
The contrasting histories of the western and eastern shores of the North Atlantic Ocean provide an excellent opportunity to consider the implications of past events for present ecological processes and the functioning of marine ecosystems. Similarities and differences in assemblage composition have been driven by large‐scale events, such as the trans‐Arctic interchange, which has shaped the species pool, and cycles of glaciation, which have determined phases of local or regional extinction and colonization. More recently, anthropogenically induced invasions and local extinctions have significantly altered biogeographic distributions. Here we consider for both hard and soft substrata how the presence or absence of key taxa influences the outcomes of trophic and other biological interactions, and evaluate the consequences for community structure and ecosystem functioning. On intertidal hard substratum shores, biodiversity of epilithic microphagous grazers differs across latitudinal and longitudinal scales. Diversity is high in southern Europe but declines to the north and across the Atlantic. Lower diversity and the absence of patellid limpets in Iceland and the northwest Atlantic compared to Europe result in differences in consumer pressure, and an apparent contrast in the importance of herbivory vs. competitive interactions and predation pressure as community structuring processes. Interestingly, despite differences in “process,” community patterns are remarkably similar between the east and west. On soft sediment shores, there are conspicuous geographic differences in importance of bioturbators and large digging predators. Hemichordates can be abundant and important infaunal bioturbators in the western Atlantic, but they generally play a much reduced role in the eastern Atlantic. In addition, the number and diversity of digging predators on western Atlantic shores is high; the horseshoe crab, swimming portunid crabs, large whelks, excavating waterfowl, and an abundance of skates and rays exert intense predation pressure and associated biogenic disturbance to sediments. In Europe, except for excavating waterfowl these taxa are rare or absent. Thus, the importance of large, biological agents of disturbance is lower on European shores as a consequence of both recent anthropogenic pressure and natural processes over larger time scales. Consideration of key structuring taxa over the Atlantic shows that human‐mediated transport has had considerable influence. Faunas on both sides of the Atlantic are becoming more similar to the point that some of the key differences in assemblage composition and hence community organization have blurred. Recent introductions as well as planned experimental manipulations provide the opportunity to understand the role of species identity in determining community structure and ecosystem functioning over large spatial scales; the North Atlantic may be an ideal test system to explore these areas.

From Genes to Ecosystems: The Genetic Basis of Condensed Tannins and Their Role in Nutrient Regulation in a Populus Model System - Jennifer A. Schweitzer; Michael D. Madritch; Joseph K. Bailey; Carri J. LeRoy; Dylan G. Fischer; Brian J. Rehill; Richard L. Lindroth; Ann E. Hagerman; Stuart C. Wooley; Stephen C. Hart; Thomas G. Whitham (Ecosystems, 2008)

Double-averaged velocity and stress distributions for hydraulically-smooth and transitionally-rough turbulent flows - Stuart M. Cameron; Vladimir I. Nikora; Stephen E. Coleman (Acta Geophysica, 2008)

Nocturnal foraging by great skuas Stercorarius skua: implications for conservation of storm-petrel populations - Stephen C. Votier; Jonathan E. Crane; Stuart Bearhop; Ana de León; Claire A. McSorley; Eduardo Mínguez; Ian P. Mitchell; Matthew Parsons; Richard A. Phillips; Robert W. Furness (Journal of Ornithology, 2006)

Testing metabolic ecology theory for allometric scaling of tree size, growth and mortality in tropical forests - Helene C. Muller‐Landau; Richard S. Condit; Jerome Chave; Sean C. Thomas; Stephanie A. Bohlman; Sarayudh Bunyavejchewin; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; Kyle E. Harms; Terese Hart; et al. (Ecology Letters, 2006)
The theory of metabolic ecology predicts specific relationships among tree stem diameter, biomass, height, growth and mortality. As demographic rates are important to estimates of carbon fluxes in forests, this theory might offer important insights into the global carbon budget, and deserves careful assessment. We assembled data from 10 old‐growth tropical forests encompassing censuses of 367 ha and > 1.7 million trees to test the theory's predictions. We also developed a set of alternative predictions that retained some assumptions of metabolic ecology while also considering how availability of a key limiting resource, light, changes with tree size. Our results show that there are no universal scaling relationships of growth or mortality with size among trees in tropical forests. Observed patterns were consistent with our alternative model in the one site where we had the data necessary to evaluate it, and were inconsistent with the predictions of metabolic ecology in all forests.

Comparing tropical forest tree size distributions with the predictions of metabolic ecology and equilibrium models - Helene C. Muller‐Landau; Richard S. Condit; Kyle E. Harms; Christian O. Marks; Sean C. Thomas; Sarayudh Bunyavejchewin; George Chuyong; Leonardo Co; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; et al. (Ecology Letters, 2006)
Tropical forests vary substantially in the densities of trees of different sizes and thus in above‐ground biomass and carbon stores. However, these tree size distributions show fundamental similarities suggestive of underlying general principles. The theory of metabolic ecology predicts that tree abundances will scale as the −2 power of diameter. Demographic equilibrium theory explains tree abundances in terms of the scaling of growth and mortality. We use demographic equilibrium theory to derive analytic predictions for tree size distributions corresponding to different growth and mortality functions. We test both sets of predictions using data from 14 large‐scale tropical forest plots encompassing censuses of 473 ha and > 2 million trees. The data are uniformly inconsistent with the predictions of metabolic ecology. In most forests, size distributions are much closer to the predictions of demographic equilibrium, and thus, intersite variation in size distributions is explained partly by intersite variation in growth and mortality.

A continental scale evaluation of the role of limpet grazing on rocky shores - Ross A. Coleman; Antony J. Underwood; Lisandro Benedetti-Cecchi; Per Åberg; Francisco Arenas; Julio Arrontes; João Castro; Richard G. Hartnoll; Stuart R. Jenkins; José Paula; Paolo Della Santina; Stephen J. Hawkins (Oecologia, 2006)

Identifying and Mapping Surface Amorphous Domains - Stuart Ward; Mark Perkins; Jianxin Zhang; Clive J. Roberts; Claire E. Madden; Shen Y. Luk; Nikin Patel; Stephen J. Ebbens (Pharmaceutical Research, 2005)

Persistence of aquatic refugia between flow pulses in a dryland river system(Cooper Creek, Australia) - Stephen K. Hamilton; Stuart E. Bunn; Martin C. Thoms; Jonathan C. Marshall (Limnology and Oceanography, 2005)
In many dryland rivers with intermittent flow, relatively deep segments of the river channel serve as refugia for aquatic life during protracted intervals between flows. Semipermanent channel segments are known as waterholes in the semiarid Cooper Creek system of western Queensland. Fractional water loss by evaporation was estimated in 15 Cooper waterholes from the increase in conservative ion (Na + and Cl − ) concentrations and independently from evaporative fractionation of oxygen and hydrogen isotopes in water. The major solute chemistry and isotope results indicated that evaporative water loss controlled the water levels between flows and that the surface waters were effectively isolated from underlying groundwater that had a distinctive chemical and isotopic composition. Fractional water loss rates combined with stage‐volume relationships for each basin showed a mean evaporative loss rate of 2.1 m yr −1 ; during that time (April‐October 2002), pan evaporation averaged 2.5 m yr −1 . Site‐specific extrapolation of those estimated evaporative loss rates indicated that the waterholes would dry to 10% of their bankfull volumes in 6‐23 months, although those estimates were based on sampling in 2002, when pan evaporation rates were 18% higher than the long‐term mean. These persistence times show the importance of occasional, irregular flow pulses in sustaining these aquatic refugia; the desiccation of waterholes could become more common if future water withdrawals reduce the frequency and intensity of river flows to the point where they occur less often than annually.

Population resistance to climate change: modelling the effects of low recruitment in open populations - Carl Johan Svensson; Stuart R. Jenkins; Stephen J. Hawkins; Per berg (Oecologia, 2005)

Modeling Sustainability of Arctic Communities: An Interdisciplinary Collaboration of Researchers and Local Knowledge Holders - Jack A. Kruse; Robert G. White; Howard E. Epstein; Billy Archie; Matt Berman; Stephen R. Braund; F. Stuart Chapin; Johnny Charlie; Colin J. Daniel; Joan Eamer; Nick Flanders; Brad Griffith; et al. (Ecosystems, 2004)

Interactions among dissolved organic carbon, microbial processes, and community structure in the mesopelagic zone of the northwestern Sargasso Sea - Craig A. Carlson; Stephen J. Giovannoni; Dennis A. Hansell; Stuart J. Goldberg; Rachel Parsons; Kevin Vergin (Limnology and Oceanography, 2004)
At the Bermuda Atlantic Time‐Series Study (BATS) site, the field observations of dissolved organic carbon (DOC) dynamics indicate that seasonally produced “semilabile” DOC is resistant to rapid microbial degradation in the surface waters but available for microbial remineralization once it is delivered into the mesopelagic zone after convective overturn. In this study, we employed an experimental simulation of convective overturn events to determine whether the remineralization of semilabile DOC would occur in a controlled laboratory setting. Seawater culture experiments were conducted in which surface (≤10 m) and mesopelagic (250 m) 0.2‐mm filtrates were inoculated with unfiltered water from ≤10 and 250 m in an assortment of combinations to simulate various mixtures of nutrients, DOC quantity and quality, and microbial assemblages. Results indicate that (1) microbial inocula from the upper euphotic zone were incapable of remineralizing the seasonally accumulated semilabile DOC (µmol C L −1 resolution) on the timescales of the incubations; (2) the utilization of semilabile DOC was greatest when the inoculum source was from 250 m and the filtrate source was from the upper 10 m; and (3) the decrease in bacterioplankton diversity, estimated with the Shannon‐Wiener diversity index, was greater in treatments in which inoculum from 250 m was mixed with filtrate from 10 m than in treatments in which the surface inoculum was mixed with the surface filtrate. Our findings are that a portion of the surface semilabile DOC can be metabolized by microorganisms in a laboratory setting and that mesopelagic nutrients alone are insufficient to stimulate DOC drawdown >1.3 µmol L −1 . Transformations of microbial community structure were associated with the drawdown of surface DOC in simulated mixing events and suggest that microbial community structure is a factor in surface‐layer DOC dynamics.

Impact of Agricultural Land‐use Change on Carbon Storage in Boreal Alaska - José M. Grünzweig; Stephen D. Sparrow; Dan Yakir; F. Stuart Chapin (Global Change Biology, 2004)
Climate warming is most pronounced at high latitudes, which could result in the intensification of the extensively cultivated areas in the boreal zone and could further enhance rates of forest clearing in the coming decades. Using paired forest‐field sampling and a chronosequence approach, we investigated the effect of conversion of boreal forest to agriculture on carbon (C) and nitrogen (N) dynamics in interior Alaska. Chronosequences showed large soil C losses during the first two decades following deforestation, with mean C stocks in agricultural soils being 44% or 8.3 kg m −2 lower than C stocks in original forest soils. This suggests that soil C losses from land‐use change in the boreal region may be greater than those in other biomes. Analyses of changes in stable C isotopes and in quality of soil organic matter showed that organic C was lost from soils by combustion of cleared forest material, decomposition of organic matter and possibly erosion. Chronosequences indicated an increase in C storage during later decades after forest clearing, with 60‐year‐old grassland showing net ecosystem C gain of 2.1 kg m −2 over the original forest. This increase in C stock resulted probably from a combination of large C inputs from belowground biomass and low C losses due to a small original forest soil C stock and low tillage frequency. Reductions in soil N stocks caused by land‐use change were smaller than reductions in C stocks (34% or 0.31 kg m −2 ), resulting in lower C/N ratios in field compared with forest mineral soils, despite the occasional incorporation of high‐C forest‐floor material into field soils. Carbon mineralization per unit of mineralized N was considerably higher in forests than in fields, which could indicate that decomposition rates are more sensitive in forest soils than in field soils to inorganic N addition (e.g. by increased N deposition from the atmosphere). If forest conversion to agriculture becomes more widespread in the boreal region, the resulting C losses (51% or 11.2 kg m −2 at the ecosystem level in this study) will induce a positive feedback to climatic warming and additional land‐use change. However, by selecting relatively C‐poor soils and by implementing management practices that preserve C, losses of C from soils can be reduced.

Assessing the diet of great skuas, Catharacta skua, using five different techniques - Stephen C. Votier; Stuart Bearhop; Aidan MacCormick; Norman Ratcliffe; Robert W. Furness (Polar Biology, 2003)

The use of sectioned otoliths to age barramundi (Lates calcarifer) (Bloch, 1790) [Centropomidae] - Ivor G. Stuart; Stephen C. McKillup (Hydrobiologia, 2002)

Primary productivity of planet earth: biological determinants and physical constraints in terrestrial and aquatic habitats - Richard J. Geider; Evan H. Delucia; Paul G. Falkowski; Adrien C. Finzi; J. Philip Grime; John Grace; Todd M. Kana; Julie La Roche; Stephen P. Long; Bruce A. Osborne; Trevor Platt; I. Colin Prentice; et al. (Global Change Biology, 2001)

The Leishmania genome project: new insights into gene organization and function - Peter J. Myler; Stephen M. Beverley; Angela K. Cruz; Deborah E. Dobson; Alasdair C. Ivens; Paul D. McDonagh; Rentala Madhubala; Santiago Martinez-Calvillo; Jeronimo C. Ruiz; Alka Saxena; Ellen Sisk; Susan M. Sunkin; et al. (Medical Microbiology and Immunology, 2001)

Expression, purification and characterization of cytochrome P450 Biol: a novel P450 involved in biotin synthesis in Bacillus subtilis - Amanda J. Green; Stuart L. Rivers; Myles Cheesman; Graeme A. Reid; Luca G. Quaroni; Iain D. G. Macdonald; Stephen K. Chapman; Andrew W. Munro (JBIC Journal of Biological Inorganic Chemistry, 2001)

Susceptibility of Antarctic krill ( Euphausia superba Dana) to ultraviolet radiation - Stuart J. Newman; Stephen Nicol; David Ritz; Harvey Marchant (Polar Biology, 1999)

Identification of an assimilatory nitrate reductase in mutants of Paracoccus denitrificans GB17 deficient in nitrate respiration - Heather J. Sears; Phillip J. Little; D. J. Richardson; B. C. Berks; Stephen Spiro; Stuart J. Ferguson (Archives of Microbiology, 1997)

Renal perfusion dynamics during preservation - Stephen W. Flax; John G. Webster; Stuart J. Updike; David T. Uehling (Annals of Biomedical Engineering, 1978)

Two models for the evolution of polygyny - Stuart A. Altmann; Stephen S. Wagner; Sarah Lenington (Behavioral Ecology and Sociobiology, 1977)